Mouse Models of c-myc Deregulation Driven by IgH Locus Enhancers as Models of B-Cell Lymphomagenesis - Ferrad, Melissa; Ghazzaui, Nour; Issaoui, Hussein; Cook-Moreau, Jeanne; Denizot, Yves (Frontiers in Immunology, 2020)
Chromosomal translocations linking various oncogenes to transcriptional enhancers of the immunoglobulin heavy chain (IgH) locus are often implicated as the cause of B-cell malignancies. Two major IgH transcriptional enhancers have been reported so far. The Emu enhancer located upstream of the Calpha gene controls early events in B-cell maturation such as VDJ recombination. The 3’ regulatory region (3’RR) located downstream from the Calpha gene controls late events in B-cell maturation such as IgH transcription, somatic hypermutation and class switch recombination. Convincing demonstration of the essential contributions of both Emu and 3’RR in B-cell lymphomagenesis has been provided by transgenic and knock-in animal models which bring the oncogene c-myc under Emu/3’RR transcriptional control. This short review summarizes the different mouse models so far available and their interests/limitations for progress in our understanding of human c-myc-induced B-cell lymphomagenesis.